Cast aluminium matrix composites modified with using FSP process – Changing of the structure and mechanical properties. (1st December 2015) - Kurtyka, Pawel; Rylko, Natalia; Tokarski, Tomasz; Wójcicka, Anna; Pietras, Adam
Abstract: The aim of this study was to explain the influence of the plastic deformation generated in friction stir processing on the changing concentration and distribution of SiC reinforcement particles in the cast composite A339/SiC/p, as well as determine its mechanical properties. Aluminum matrix reinforced with 10% vol. SiC particles was modified using friction stir processing method. Changing of distribution of the reinforcement particles was calculated and analysed using new mathematical RVE theory with Mityushev–Eisenstein–Rayleigh sums (M-sum) and PointSel software. The mechanical properties were determined on the basis of compression and hardness tests.The significant changes in the concentration and distribution of SiC particles were observed. Mechanical testing of selected deformed areas showed significant differences in the values of the plastic flow stress and hardness in thermomechanical hardening areas, approximately from about 30–40%.